Ukrainian medium sized business in terms of global competitive environment: national specifics, tendencies and main problems of development - Tulku, Y.I.; Kapturenko, N.G. (Економічний вісник Донбасу, 2010)
The article examines the essence and main characteristics of Ukrainian medium-sized business. The authors analyses the role SMEs sector, especially the middle sector in the economic development. The article also estimates the condition of medium business, main tendencies of development and perspectives. The author summarizes essential factors that influence on mediumsized business development. Key words: medium-sized business, economic development, business classification, productivity.